El cariotipo fundamental de Alstroemeria versicolor Ruiz et Pav. (Alstroemeriaceae) The fundamental karyotype of Alstroemeria versicolor Ruiz et Pav. (Alstroemeriaceae) - CARLOS M BAEZA (Universidad de Concepción, 2011)
The karyotype of Alstroemeria versicolor Ruiz et Pav. from Chile was described. The species has a karyotype 2n = 2x = 16, and the haploid formula was 1m + 3sm + 1st + 2st-sat + 1t. The reported karyotype is asymmetric (AsK % = 65.9 and Syi = 51.8%). The results are discussed including data of others species.